1986
DOI: 10.1159/000216041
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Trial Concerning Hyper- and Normoprolactinemia and the Use of Bromoergocryptine in Patients with Metastatic Breast Cancer

Abstract: This prospective trial was designed to help in selecting therapy for patients with elevated and normal plasma prolactin. Ninety-two patients entered this trial, of whom 86 were evaluable for final analysis. Hyperprolactinemic patients (n = 31) were randomized to receive VAC/FMC chemotherapy with or without bromoergocryptine. Normoprolactinemic patients with ‘low risk’ metastatic disease (disease-free interval > 30 months, ER/PR positive or unknown) were treated with medroxyprogesterone acetate or VAC/FMC chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…At the therapeutic level, only a few trials have been reported, and the results obtained from the treatment of breast or prostate cancer patients with dopamine agonists are disappointing. Although bromocriptine was shown to normalize PRL levels in metastatic breast cancer and prostate carcinoma patients, it was not found to provide significant benefit to breast cancer (70,71) or prostate cancer (72) patients. One report indicated that lowering PRL levels using bromocriptine improved the antitumor actions of chemotherapeutic agents such as Taxotere (73), which is an interesting issue that requires confirmation.…”
Section: Epidemiological Evidencementioning
confidence: 99%
“…At the therapeutic level, only a few trials have been reported, and the results obtained from the treatment of breast or prostate cancer patients with dopamine agonists are disappointing. Although bromocriptine was shown to normalize PRL levels in metastatic breast cancer and prostate carcinoma patients, it was not found to provide significant benefit to breast cancer (70,71) or prostate cancer (72) patients. One report indicated that lowering PRL levels using bromocriptine improved the antitumor actions of chemotherapeutic agents such as Taxotere (73), which is an interesting issue that requires confirmation.…”
Section: Epidemiological Evidencementioning
confidence: 99%
“…This had particular weight in view of the extensive and long history of use of antipsychotic dopamine antagonists known pharmacologically to elevate prolactin. Additionally, prolactin-suppressing dopamine agonist drugs such as bromocriptine were shown to be ineffective in breast cancer treatment (Fritze et al, 1986;Bonneterre et al, 1988;Holtcamp and Nagel, 1988), which strengthened the view that prolactin had no clinical relevance to breast cancer despite early evidence that hyperprolactinaemia was correlated with poor breast cancer prognosis (Holtkamp et al, 1984;Wang et al, 1986). Thus, there was little evidence of an effect of prolactin in human breast cancer (as assessed by centrally acting dopaminemodulating drugs) versus a wealth of experience of prolactin and mammary carcinogenesis in rodents, because the rat had been used as a model of mammary carcinogenesis in cancer research.…”
Section: Introductionmentioning
confidence: 99%
“…Mershon et al , ; Ben‐Jonathan et al , ; Liby et al , ; and see Bhatavdekar et al , on prolactin as a local growth promoter in breast cancer patients). It has been noted (Clevenger et al , ; Harvey et al , ) that it was probably the lack of control of local autocrine/paracrine prolactin secretion from tumors/breast epithelium that prevented efficacy of dopamine agonist prolactin‐lowering drugs in early patient trials (see Fritze et al , ; Holtkamp and Nagel, ), although some success in improving breast cancer treatment has been achieved by lowering systemic prolactin (Lissoni et al , ; Frontini et al , ).…”
Section: The Prolactin Receptor As a Pharmacological Target For Breasmentioning
confidence: 99%